SOLAR ASSISTED DRYING SYSTEM - M. Yahya (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2012)
A solar assisted drying system has been designed, fabricated, and evaluated. The main components of the drying system consist of a solar collector, an energy storage tank, an auxiliary heater, two blowers, two adsorber columns, two water-air heat exchanger, two water circulating pumps, a drying chamber and other ancillary equipment. The solar collectors used were 60-evacuated heat pipes tube arranged in parallel with total area of 6 m2 . The area of absorber in tube each individual was 0.1 m2 , and distance between the tubes was 7.1 cm. The objective of this study is to evaluate the contribution of solar energy to drying system for drying Centella Asiatica L (heat sensitive product). A computer program was developed in MATLAB software to calculate the contribution of solar energy to drying system. The results found that the total energy required by drying system for drying Centella Asiatica L from initial weigh of 3 kg to final weigh of 0.37 kg over drying time of about 12 hours at an air velocity is 3.25 m/s was found 47609 kJ. This energy contributed by solar collector, auxiliary heater and pump and blower of about 25315 kJ, 17829 kJ and 4464 kJ, respectively. The maximum values of solar fraction (SF) was found 97 %.